Qualitative analysis of luxury brand charisma - Hatton-Jones, Siobhan (2019)
The purpose of this study is to conceptualise the term ‘luxury brand charisma’, and thus provide a working definition and identify key themes and sub themes that can be used to inform the secondary stage of this research, being scale development. The research paradigm chosen was pragmatic as this study is part of mixed methods research and pragmatism allows for inductive and deductive reasoning through qualitative and quantitative methods (Saunders & Thornhill 2012). As part of a mixed methods research, the qualitative phase investigates the phenomenon from a consumer perspective. This research employed a qualitative methodology utilising 2 semi-structured focus groups with a sample size of 9 participants, utilising a convenience sampling method from general consumer population. Data was coded using NVivo and analysed using narrative and thematic analysis techniques, by analysing the words and meanings across various sets of data (Braun and Clarke 2006, p. 86). Findings have shown two key emergent themes from the focus groups, which are supported through the findings within the luxury and charisma literature. The limitations of this research is that it is only using a limited sample comprising of 9 participants from an Australian sample. This research adds value by making significant contributions by extending and building theory; holds managerial implications for policymakers and brand managers in shaping and communicating brand charisma; additionally findings can be used in the early stages of scale development and research framework.